2021
DOI: 10.1111/asj.13652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibrolytic enzymes in total mixed ration containing urea‐molasses‐treated sugarcane bagasse on the performance of lactating Holstein–Friesian crossbred cows

Abstract: The aim of this study was to determine the effect of different levels of fibrolytic enzyme on nutrient utilization and milk production in dairy cows. Four multiparous early-to-mid-lactation Holstein-Friesian crossbred cows were randomly allocated in a 4 Â 4 Latin square design. Cows were fed a balanced total mixed ration (TMR) on a dry matter (DM) basis containing 0, 1.2, 2.4, and 3.6 g/kg DM of fibrolytic enzyme in TMR, where the TMR comprises 60% concentrate supplemented with a fibrolytic enzyme at 0, 2, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Besides, it increases the net energy‐lactation (NE L ) by 12%. In vivo study confirmed that EFE improves milk production (Lunsin et al., 2021 ; Mohamed et al., 2013 ). Also, at this dose, the EFE1 increased in microbial production of crude protein by 7%.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Besides, it increases the net energy‐lactation (NE L ) by 12%. In vivo study confirmed that EFE improves milk production (Lunsin et al., 2021 ; Mohamed et al., 2013 ). Also, at this dose, the EFE1 increased in microbial production of crude protein by 7%.…”
Section: Discussionmentioning
confidence: 72%
“…However, it decreases the potential of gas production. The inhibitory effect of EFE on high dose has also been proven in vivo (Lunsin et al, 2021) and in vitro b). This phenomenon might be explained by the fact that excessive doses of enzymes mask the surface of feed particles, which reduce the microorganisms' adhesion to the substrate and subsequent fermentation (McAllister et al (2000)).…”
Section: Discussionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Statistical analysis of the data on total solids per cent revealed that there was no significant difference (p>0.05) between three treatments in any of the fortnights. In agreement with the results of the present study, Lunsin et al (2021) did not observe any effect on milk total solids content, when four levels of fibrolytic enzymes (0, 1.2, 2.4, and 3.6 g/ kg DM of TMR) having 4900 units cellulase, 18000 units of xylanase, 10000 units of betaglucanase and 17000 units amylase activities, when fed to lactating Holstein cows. Similarly, Miachieo and Thakur (2007) did not observe any effect on milk total solids content in lactating Sahiwal cows fed with wheat straw based TMR supplemented with a one : one mixture of cellulase and xylanase @ 1.5 g/kg DM and the values ranged from 13.3 to 13.4 per cent.…”
Section: Milk Compositionsupporting
confidence: 93%
“…Regarding our data, ruminal NH 3 -N concentrations did not differ between sheep fed FSB with and without additives. This suggests that further study should focus on the optimal level of urea that can be added in order to enhance the ruminal NH 3 -N [41,42]. The proportions of acetic acid and propionic acid did not differ among treatments.…”
Section: Fsb Affected Blood Parameters and Ruminal Fermentationmentioning
confidence: 90%